Effect of Rapid Maxillary Expansion on Blood Flow at Midpalatal Suture Region - Ali Altuğ Bıçakçı (Galenos Yayinevi, 2006)
The aim of this study was to evaluate the blood flow at the midpalatal suture with laser Doppler flowmetry during rapid maxillary expansion (RME) and following retention period. The study was carried out on 11 patients, at 11,3 14,6 years of age and treated with bonded RME appliance. Records were taken before expansion (T1), after expansion (T2) and after 3 months retention period (T3). Blood flow was increased by 50% at the end of expansion compared with initial. After three months of retention, although still higher, blood flow returned almost to its original level. The results suggest that, inflammation, destructive and regenerative processes were on the increase during expansion and were decreasing during retention period.